Estimating long-term health risks after breast cancer radiotherapy: merging evidence from low and high doses - Simonetto, Cristoforo; Wollschläger, Daniel; Kundrát, Pavel; Ulanowski, Alexander; Becker, Janine; Castelletti, Noemi; Güthlin, Denise; Shemiakina, Elena; Eidemüller, Markus (Radiation and environmental biophysics, 2021)
In breast cancer radiotherapy, substantial radiation exposure of organs other than the treated breast cannot be avoided, potentially inducing second primary cancer or heart disease. While distant organs and large parts of nearby ones receive doses in the mGy-Gy range, small parts of the heart, lung and bone marrow often receive doses as high as 50 Gy. Contemporary treatment planning allows for considerable flexibility in the distribution of this exposure. To optimise treatment with regards to long-term health risks, evidence-based risk estimates are required for the entire broad range of exposures. Here, we thus propose an approach that combines data from medical and epidemiological studies with different exposure conditions. Approximating cancer induction as a local process, we estimate organ cancer risks by integrating organ-specific dose-response relationships over the organ dose distributions. For highly exposed organ parts, specific high-dose risk models based on studies with medical exposure are applied. For organs or their parts receiving relatively low doses, established dose-response models based on radiation-epidemiological data are used. Joining the models in the intermediate dose range leads to a combined, in general non-linear, dose response supported by data over the whole relevant dose range. For heart diseases, a linear model consistent with high- and low-dose studies is presented. The resulting estimates of long-term health risks are largely compatible with rate ratios observed in randomised breast cancer radiotherapy trials. The risk models have been implemented in a software tool PASSOS that estimates long-term risks for individual breast cancer patients.
Keywords: Software; nádory prsu; Humans; Risk Assessment; Lung Neoplasms; kouření; leukemie; Breast Neoplasms; Heart Diseases; Smoking; Leukemia; software; nádory plic; nemoci srdce; ženské pohlaví; hodnocení rizik; vztah dávky záření a odpovědi; lidé; Dose-Response Relationship, Radiation; teoretické modely; Models, Theoretical; Female